Strategi Pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) dalam Industri Keripik Beras Di Desa Kalumpang Kedung Bulus: Studi Kasus Analisis Potensi Pasar dan Inovasi Produk - Gagah Dwiki Putra Aryono (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
This research raises the theme of strategies for developing Micro, Small and Medium Enterprises (MSMEs) in the rice chips industry in Kalumpang Kedung Bulus Village. The aim of this research is to analyze market potential and product innovation as key components in the growth of MSMEs in the rice chips industry. The research method used is a case study with a qualitative approach. Data was collected through in-depth interviews with rice chips MSME owners, field observations, and analysis of documents related to the industry and market. The research results show that MSMEs in Kalumpang Kedung Bulus Village have adopted a product diversification strategy and focused on innovation in taste, packaging and product quality. Market potential analysis identified significant consumer demand for healthy snacks, as well as a preference for local products. The implication of this research is the need to develop policies that support the empowerment of MSMEs through management training, access to financing, and wider market access through the use of digital platforms. Thus, this research provides practical guidance for MSMEs in optimizing market potential and innovating products in order to achieve sustainable growth in the rice chips industry in the region.